HASIL KARANGAN DESKRIPSI MENGGUNAKAN KOMIK STRIP PADA SITUS WWW.HANDSCHUHFISCH.DE SEBAGAI MEDIA PEMBELAJARAN KETERAMPILAN MENULIS SISWA KELAS XII SEMESTER 1 SMA NEGERI 8 SURABAYA - KHOTIMAH, KHUSNUL (LATERNE, 2018)
Abstract There are varieties of problems in writing. According to a discussion with the German teacher at SMAN 8 Surabaya, it is found that the students of XII MIA 2 are often having difficulties in determining ideas. The students also have low level of proficiency in diktions and grammatics. Comic strips combine pictures and texts which contains of information needed in essays writing. So the researcher is interested to examine comic strips as a media to improve the students? writing skills. The purpose of this study is to describe the scores of 12th graders of the first semester at SMAN 8 Surabaya in writing descriptive texts using comic strips as a learning media. The data are collected from the students? writing test which was performed 3 times. The data then being compared and analyzed to draw a conclusion. Based on the results, 59% of the students? scores were gained, 12% were fluctuated, 9% persisted and the 19% descended. In consonance with that, comic strips can be used as an alternative media to help the students to advance their writing skills. Keywords: Learning Media, Comic Strips, Writing Skills.